Model Hexahelix sebagai Strategi Pengembangan Eco-Cultural Tourism di Kabupaten Malang: Studi pada Destinasi Wisata Gastronomi Tomboan Ngawonggo - Agatha, Satifa; Yudha Pratama, Andhika (Jurnal Abdimas Pariwisata, 2025)
Hexahelix Model as a Strategy for Developing Eco-Cultural Tourism in Malang District (Study onTomboan Ngawonggo Gastronomic Tourism Destination) This article analyzes the implementation of the Hexahelix collaboration model in the development of the Tomboan Ngawonggo gastronomic tourism destination. Using a qualitative descriptive approach, the research explores tourism potential, stakeholder roles, and resistance dynamics through observation, interviews, and documentation. The findings indicate that the management of Tomboan Ngawonggo has adopted Hexahelix principles, although the Kaswangga tourism awareness group (Pokdarwis) still plays a dominant role. Collaboration with external parties such as the government, media, and tourists also shows positive synergy. SWOT analysis reveals the forms of resistance, including strengths, weaknesses, obstacles, and opportunities for the destination. This collaborative model supports the development of eco-cultural tourism and promotes sustainable and inclusive tourism practices. The results are expected to serve as an evaluative reference for relevant stakeholders in advancing eco-cultural tourism areas through a more collaborative and strategic approach, particularly in encouraging sustainable tourism in Malang Regency that leverages local potential and inclusive stakeholder engagement.